Colorectal Cancer-Infiltrating Regulatory T Cells: Functional Heterogeneity, Metabolic Adaptation, and Therapeutic Targeting - Aristin Revilla, Sonia; Kranenburg, Onno; Coffer, Paul J. (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is a heterogeneous disease with one of the highest rates of incidence and mortality among cancers worldwide. Understanding the CRC tumor microenvironment (TME) is essential to improve diagnosis and treatment. Within the CRC TME, tumor-infiltrating lymphocytes (TILs) consist of a heterogeneous mixture of adaptive immune cells composed of mainly anti-tumor effector T cells (CD4+ and CD8+ subpopulations), and suppressive regulatory CD4+ T (Treg) cells. The balance between these two populations is critical in anti-tumor immunity. In general, while tumor antigen-specific T cell responses are observed, tumor clearance frequently does not occur. Treg cells are considered to play an important role in tumor immune escape by hampering effective anti-tumor immune responses. Therefore, CRC-tumors with increased numbers of Treg cells have been associated with promoting tumor development, immunotherapy failure, and a poorer prognosis. Enrichment of Treg cells in CRC can have multiple causes including their differentiation, recruitment, and preferential transcriptional and metabolic adaptation to the TME. Targeting tumor-associated Treg cell may be an effective addition to current immunotherapy approaches. Strategies for depleting Treg cells, such as low-dose cyclophosphamide treatment, or targeting one or more checkpoint receptors such as CTLA-4 with PD-1 with monoclonal antibodies, have been explored. These have resulted in activation of anti-tumor immune responses in CRC-patients. Overall, it seems likely that CRC-associated Treg cells play an important role in determining the success of such therapeutic approaches. Here, we review our understanding of the role of Treg cells in CRC, the possible mechanisms that support their homeostasis in the tumor microenvironment, and current approaches for manipulating Treg cells function in cancer.